Preparation, Characterization and Manipulation of Conjugates between Gold Nanoparticles and DNA - Eidelshtein, Gennady (Nanomaterials (Basel), 2016)
Here we described the preparation and characterization by atomic force microscopy of dumbbell-shaped conjugates between 450 bp double-stranded DNA polymer, poly(dG)-poly(dC), and 5 nm gold nanoparticles (GNPs). We have demonstrated that the size of the nanoparticles in the conjugates can be increased in a controlled fashion. Application of the conjugates for measuring the electrical conductivity of DNA is discussed.